(untitled) (American Journal of Islam and Society, 2004)
Flowers of Galilee breaks new ground in modern political discourse. This book recommends a democratic one-state solution in all of historical Palestine and the return of the Palestinians to rebuild their villages. The beautiful front cover painting by Suleiman Mansour of Jerusalem lovingly depicts a Palestinian family, children seated on a donkey, walking past a hill covered with olive trees. Similarly, Israel Shamir’s essays portray the peaceful, pastoral landscape of the Holy Land and the humanity of its inhabitants, juxtaposed against the ugliness and inhumanity of Jewish racism. These thought-provoking essays, written in Jaffa during the al-Aqsa Intifada in 2001-02, call for Jews to leave their sense of exclusivity and plead for human equality. The author, a Russian immigrant to Israel in 1969, followed his meditations to their inevitable conclusion, renounced Judaism, and was baptized in the Palestinian Orthodox Christian Church of Jerusalem. A brilliant storyteller with a vast knowledge of history, he discusses current events and their global implications with brutal honesty and tenderness. His clear insights and lyrical use of language to illustrate social, religious, and political complexities make him the Khalil Gibran of our time. An important chapter, “The Last Action Heroes,” memorializes the Spring 2002 siege of Bethlehem. The Israeli army surrounded 40 monks and priests and 200 Palestinians seeking refuge in the Church of Nativity. For a month, “people starved ... Stench of corpses and of infected wounds filled the old church” (p. 63). The UN did nothing, but a few International Solidarity Movement activists from America and Europe, including the author’s son, broke the siege. One group distracted the soldiers while the others rushed into the church’s gates, brought food and water, and helped negotiate a surrender. Shamir deconstructs the legal fictions of the state of Israel and the elusive Palestinian state: “Israelis who would like to live in peace with their Palestinian neighbors ... cannot counteract the raw muscle of the American Jewish leadership” (p.179). He further dissects the Jewish Holocaust cult and other Zionist public relations tactics. He exposes the two-state solution as a political bluff, calls on the world to cut off aid to Israel, and admonishes the Muslim world for indulging in usury ...